Predicting variables of alcohol consumption among Spanish adolescents - Ruiz Juan, Francisco; Ruiz Risueño, Jorge (Anales de Psicología / Annals of Psychology, 2011)
The aim will be to contribute to building a model of alcohol consumption among young people in Compulsory Secondary (ESO) and Secondary Not compulsory Education (ESPO), depending on indepen-dent variables like sex, age, practice during free time, Finnish index of physical activity and sport, consumer behavior in family and consumption of tobacco. 6170 students were tested, representing Almería, Granada and Murcia regions with a range of age from 12 to 19 years old. Descriptive analysis and multinomial logistic regression were used for testing relation-ship between variables and to calculate odds ratio (OR). Results show males consume alcohol in major measurement that the women, being increased with the age. The habitual practice of physical activity, in the quantity and frequency that is in the habit of being recommended to support the health, is an element that is associated with a lower prevalence of alcohol use. Family environment drinker stands as a risk factor for alcohol consumption of subjects, especially outstanding are the figures of brothers and sisters. The consumption of tobacco appears as the principal factor of risk for the consumption and ingestion of alcohol.